Utilizing WhatsApp As An Educational Technology Tool In Improving Students’ Speaking For ESP Instruction - Luana Sasabone; Sunarlia Limbong; Fien Pongpalilu; Dewi Nidia Soepriadi; Yuriatson Jubhari (CV. Eureka Murakabi Abadi, 2022)
This study is designed to develop a WhatsApp social media approach to improve students' speaking skills in English for Specific Purposes (ESP) instruction. This approach seems to stimulate students to be more involved in free speaking activities so that their speaking skills can improve and they become more being motivated. This study used Classroom Action Research (CAR) namely (1) planning, (2) actions, (3) observation, and (4) reflection. This research is focused on second semester students of in civil Engineering students so that the number of students is not much. This inspires them to focus more on researching and motivating the students themselves. With the success of Cycle II, voice note social media can be a millennial innovation for English teachers, both teachers and lecturers. It was conducted for about two cycles namely cycle I and cycle II. According to the results of speaking test, findings showed that the implementation English for Specific Purposes (ESP) in teaching had positive meaningful effect on improving students’ speaking skill after being obtained test results both cycle 1 and cycle II in civil Engineering students of UKI Paulus Makassar. It can be concluded that utilizing WhatsApp as an educational technology tool improves students’ speaking for ESP instruction in civil Engineering students of UKI Paulus Makassar.